Emerging Contaminants and Their Removal from Aqueous Media Using Conventional/Non-Conventional Adsorbents: A Glance at the Relationship Between Materials, Processes, and Technologies - Villamar-Ayala, C (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Emerging contaminants (ECs) are causing negative effects on the environment and even on people, so their removal has become a priority worldwide. Adsorption and the associated technologies where this process occurs (filtration/biofiltration) have gained great interest, due to its low cost, easy operation, and effectiveness mainly in the removal (up to 100%) of lipophilic ECs (log Kow > 4). Activated carbon continues to be the most efficient material in the removal of ECs (>850 mg/g). However, other conventional materials (activated carbon, clays, zeolites) and non-conventional materials (agro-industrial/forestry/industrial residues, nanomaterials, among others) have shown efficiencies greater than 90%. Adsorption depends on the physicochemical properties of the materials and ECs. Thus, physical/chemical/thermal modifications and nanomaterial synthesis are the most used procedures to improve adsorption capacity. A material with good adsorptive properties could be used efficiently in filtration/biofiltration technologies. Agro-industrial residues are promising alternatives to be used in these technologies, due to their high availability, low toxicity, and adsorption capacities (up to 350 mg/g). In filtration/biofiltration technologies, the material, in addition to acting as adsorbent, plays a fundamental role in operation and hydraulics. Therefore, selecting the appropriate material improves the efficiency/useful life of the filter/biofilter. © 2023 by the authors.